A Systematic Review of Prenatally Diagnosed Intra-abdominal Enteric Duplication Cysts - Fahy, Aodhnait S.; Pierro, Agostino (European Journal of Pediatric Surgery, 2019)
Introduction With improvements in prenatal ultrasound, more abdominal enteric duplication cysts (EDCs) are diagnosed prenatally. The optimal time for operative intervention is unclear. We aimed to review the evidence supporting the indication and timing of surgery for prenatally diagnosed EDCs.Materials and Methods A systematic review was performed using a defined search strategy identifying articles with inclusion criteria of prenatal diagnosis of histologically confirmed EDCs. Outcomes included (1) indications for resection (symptoms vs. prophylactic) and (2) time from birth to operative intervention.Results Of 1,590 articles screened, prenatal diagnosis of histologically confirmed EDCs was made in 68 articles, detailing indications and timing for resection for 86 patients. Thirty-five patients (41%) became symptomatic early and were resected promptly at a median of 2 days of age. Indications for intervention included bowel obstruction, volvulus, bleeding, recurrent pain and diagnostic dilemma (concern for cystic neuroblastoma). There were 51 patients (59%) who were resected prophylactically at a median of 90 days of age without interval symptoms. Symptomatic cysts had a larger mean cyst diameter. There was a difference in the anatomic distribution of asymptomatic or symptomatic EDCs–gastric duplications were more frequently asymptomatic while jejunal, proximal ileal and colonic duplications were more frequently symptomatic.Conclusion The optimal approach to EDCs diagnosed prenatally is not supported by strong evidence in the literature. Our systematic review indicates that almost half of the infants diagnosed prenatally become symptomatic early and are resected. In asymptomatic patients, close observation and delayed prophylactic resection in infancy can be considered.
Keywords: enteric duplication cysts; alimentary tract duplication; prenatal; excision; observation